The vanishing station - Ellickson, Ana (Amulet Books, 2024)
Eighteen-year-old Ruby Santos, grappling with her mother's death and financial struggles, discovers her father's secret life as a magical underworld delivery person, leading her to take over his station and jump train lines, only to realize the perilous nature of the job and the dangerous world she has entered.